Colonialism and narratives of human origins in Asia and Africa - Athreya, Sheela; Ackermann, Rebecca, Rogers (My University, 2018)
In their seminal works on postcolonialism, Edward Saïd (in Orientalism) and V.Y. Mudimbe (in The Idea of Africa) proposed that Asia and Africa, respectively, were constructs created around the notion of their otherness. Both regions were viewed as infantile, primitive, and homogenous entities that fell outside the domain of civilized (i.e. Western) humanity. These constructs shaped scientific perceptions of both continents over the course of several centuries and have continued to be operative over the last 100 years following the discovery of fossil human ancestors, particularly within the narratives of recent human origins. Here we reflect on these narratives, both in the early days of the discoveries and more recently, in the context of the othered identities of the continents more broadly. We argue that a colonialist socio-political framework has shaped the science of human origins since its inception, and that this has negatively affected the quality of this endeavour. Existing phylogenies cannot be divorced from those ideologies—even today. Indeed, while the details of human origins (e.g. when, where, who) have changed radically over time, the narrative that emerged always left one group in control, and marginalised non-Western lands and their peoples, leaving the ordering of superior and inferior more or less unchanged through the history of the discipline. More informed models of human evolution cannot be constructed until the community of voices constructing them is reworked to be more inclusive of many worldviews.
Supplemental Materials: https://osf.io/f43tr/
Keywords: decolonisation; human evolution; palaeoanthropology; scientific racism